An approximated one-quarter of IARC Group 3 (unclassifiable) chemicals fit more appropriately into IARC Group 4 (probably not carcinogenic). (17th April 2019) - Smith, Carr J; Perfetti, Thomas A
International Agency for Research on Cancer (IARC) classifies agents as to their potential carcinogenicity in humans. Monographs 1–123 categorize 120 agents as group 1 (carcinogenic to humans); 82 agents as group 2A (probably carcinogenic to humans); 311 agents as group 2B (possibly carcinogenic to humans); 499 agents as group 3 (not classifiable as to its carcinogenicity to humans); but only a single agent, caprolactam, a precursor for the manufacture of Nylon 6, fibers, and plastic as group 4 (probably not carcinogenic to humans). The evidence regarding carcinogenic potential to humans for a randomly selected sample of 100 group 3 agents was studied to determine whether the paucity of agents classified as group 4 represented the state of the scientific evidence or a reluctance on the part of IARC to classify a chemical into the lowest risk category. Of the 100 agents evaluated, a significant minority estimated at 24% did not possess structural elements of carcinogenicity, mutagenic activity in the Ames Salmonella assay or activity in a cell transformation assay. The results of this analysis suggest that the lack of agents classified as group 4 represents a reluctance on the part of IARC to place agents into the lowest category of risk. Failure to appropriately place agents into group 4 unnecessarily exhausts valuable staff resources as these low risk compounds require periodic updating of the evidentiary basis of their classification as a group 3 agent. It would be advantageous for both IARC and public health agencies if a clearer differentiation of group 3 and group 4 agents was employed.